KINERJA KONSELOR BERMARTABAT DALAM MENERAPKAN KONSELING RELASI REMAJA UNTUK MENINGKATKAN SOFT SKILL REMAJA - Sri Suryanti, Hera Heru (UNIVERSITAS SLAMET RIYADI, 2014)
The purpose of this paper is to increase the repertoire of educators in developing a pattern of educating adolescentsto achieve a perfectly mature so that it can manifest noble citizens and productive. The method of this paper includesthe study of literature and empirical studies in the field . This paper covers aspects : soft skills juvenile , adolescentcounseling relationship , counselors and dignified performance . Soft skills is a question of personal , social ,communication , and behavioral self-management , it covers a wide spectrum , namely : self-awareness , confidence ,adaptability , critical thinking , organizational awareness , attitude, initiative , emphathy , confidence , integrity , controlself-esteem, leadership, problem solving , risk-taking and time management . While the teenagers in question arechildren aged 12 to 19 years . The conclusion is that soft skills can be improved with better student through theapplication of relationship counseling adolescents , it is necessary to develop the application for counselingadolescent relationships on an ongoing basis .Keywords : Soft skills teens , dignified counselor , relationship counseling teenagers .